Improving Students’ Reading Comprehension and Critical Thinking Skills through the Implementation of QAR Strategy at SMA PGRI Dobo - Franklin Untailawan (Soshum: Jurnal Sosial dan Humaniora, 2020)
The ability to comprehend English text and to think critically in learing process is an important thing for students in English as Foreign Language (EFL) context. However, it is a common phenomena facing by the teachers in teaching and learning process that those two essential abilities are still becoming students’ problem in Indonesia. As found in SMA PGRI Dobo that is located in Aru Island Regency, Maluku Province. The use of inappropriate teaching strategy is one of the main causes contributes to these problems. This research is a Classroom Action Research which aims to overcome the problems by implementing Question-Answer Relationship (QAR) strategy. In its implementation, this resercah employs two cycles with four meetings on each cycle. There resercah subjects were 36 students of eleventh grade on sciece program. The data were obtained through mix method approach namely qualitative and quantitative method. The result of this resercah found that; 1) after the implementation of QAR strategy, the students’ reading comprehension is improved, 2) their critical thinking skills were also improved although only to the level of analyzing (C4) in blooms’ taxonomy.